1977
DOI: 10.1084/jem.146.6.1821
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte culture: induction of colonies by conditioned medium from human lymphoid cell lines.

Abstract: It has been shown that macrophage and granulocyte colonies can be induced m semisolid agar (1-3) in the presence of substances termed colony-stimulating factors (CSF), which are released predominantly by monocytes (4). However, attempts to induce formation of lymphoid colonies with CSF have so far proved unsuccessful. In the mouse, B lymphoid colonies are formed in the presence of 2-mercaptoethanol (5), and T lymphoid colonies can be induced with the plant lectins phytohemagglutinin (PHA) and concanavalin A (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

1978
1978
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
3
1
Order By: Relevance
“…This would suggest that the essential cooperative effects of autologous RBC were specific only for those lymphocyte subpopu lations capable of being stimulated in solid cultures. Kurland et al [HI and Metcalf [ 14] reported RBC to potentiate colony for mation in semisolid culture systems, while others have not found it necessary [7,11,19], Our results differ from those of Claesson et al [4] who found that SRBC in creased human T lymphocyte colony forma tion in solid cultures, but could not replace accessory leukocytes as source of essential cooperative signals. This could be due to their use of a low (l°/o) SRBC concentra tion.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…This would suggest that the essential cooperative effects of autologous RBC were specific only for those lymphocyte subpopu lations capable of being stimulated in solid cultures. Kurland et al [HI and Metcalf [ 14] reported RBC to potentiate colony for mation in semisolid culture systems, while others have not found it necessary [7,11,19], Our results differ from those of Claesson et al [4] who found that SRBC in creased human T lymphocyte colony forma tion in solid cultures, but could not replace accessory leukocytes as source of essential cooperative signals. This could be due to their use of a low (l°/o) SRBC concentra tion.…”
Section: Discussioncontrasting
confidence: 57%
“…Studies using colony formation after 5 or more days of culture cannot dis tinguish between a requirement for macro phage products in the triggering of lympho cytes from G" into the cell cycle and the maintainance of their progeny in a prolifer ative state, or both. Furthermore, with the exception of Claesson et al [4,5], all other work on colony formation has been done using semisolid culture systems [7,11,14,20,21], where some degree of early cell to cell contact was likely to occur and could play a key role in lymphocyte triggering [8, 10. 16], Such colonies might originate from small cell aggregates, rather than from sin gle cells.…”
Section: Discussionmentioning
confidence: 99%
“…This problem can be ameliorated by culturing them in ''conditioned medium'', i.e. the supernatant of cell populations [135,136]. This suggests that the cells require endocrine factors to survive, which in the context of a single cell in a vast volume of medium becomes too dilute.…”
Section: Microfluidicsmentioning
confidence: 99%
“…The positive or promoting agent for the latter system is species specific and can overcome inhibition by PGE (24). A parallel mechanism may exist for T cell precursors; in fact, a species-specific soluble agent(s) promoting T lymphocyte proliferation has been described (25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%